Why We Move: Social Mobility Behaviors of Non-Disabled and Disabled Children across Childcare Contexts - Logan, Samuel W.; Ross, Samantha Mae; Schreiber, Melynda A.; Feldner, Heather A.; Lobo, Michele A.; Catena, Michele A.; MacDonald, Megan; Galloway, James C. (Frontiers in Public Health, 2016)
Background Social mobility is defined as the co-occurrence of self-directed locomotion and direct peer interaction. Social mobility is a product of dynamic child–environment interactions and thus likely to vary across contexts (e.g., classroom, gymnasium, and playground). Purpose The purpose of this present study was to examine differences in children’s social mobility: (1) across contexts by age and (2) between non-disabled and disabled children. Method Participants (n = 55 non-disabled and three disabled children; Mage = 3.1 years, SD = 1.4) were video recorded within a university-based early learning center. Children were recorded for 20 min in each context: classroom, gymnasium, and playground. A 15-s momentary time sampling method was used to code social mobility, the simultaneous occurrence of self-directed locomotion, and direct peer interaction. This variable was calculated as percent time within each context. Results A planned Friedman’s rank ANOVA (n = 55), stratified by age, indicated that older children (3–5 years old) differed across contexts in their social mobility [χ2(2) ~ 7.3–10.5, p < 0.025], whereas younger children (1–2 years old) were similar across contexts. Social mobility was significantly lower in the classroom compared with the playground and gymnasium (with no difference between the latter contexts) for older children. Visual analysis confirmed that disabled children (n = 3) engaged in substantially less time in social mobility (average 0–1%), compared with non-disabled, age-similar peers (2–3 years old average 1–12%) across all contexts. Conclusion A substantial gap exists between non-disabled and disabled children for social mobility. There is an increase in magnitude and variability of social mobility around age three that suggests the gap between non-disabled and disabled children will continue to widen.